Dziewięćdziesięciolecie powstania uniwersytetu ludowego w Dalkach - Maliszewski, Tomasz (Biuletyn Historii Wychowania, 2011)
The article commemorates the 90th anniversary of the origin of the first peasant boarding high school based on the Scandinavian model. The author presents the endeavours of the members of People’s Libraries Society and its president – priest Antoni Ludwiczak – connected with the formation of the Great-Polish folk university. The process started already before World War I and was successfully completed in the autumn of 1921 when this educational institution began to function in Dalki in the vicinity of Gniezno. The final part of this paper is an attempt to answer two questions – the first one concerning the true significance of the high school in Dalki in the history of the Polish education of the adults in the 20th century; the second question refers to some doubts that may appear after the institution in Dalki was granted the title of the first Polish folk university.